Kalimat Efektif dalam Penulisan Akademik - Muhammad Adnan; Abdul Hanif Masyhadi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Language is the primary means of conveying information and ideas. Successful communication is largely determined by the clarity and accuracy of the message. One contributing factor to this success is the use of effective sentences. An effective sentence is defined as a sentence that conveys an idea precisely, concisely, and is easily understood by the reader or listener without creating double meanings or confusion. This paper aims to explain the meaning, characteristics, and requirements for forming effective sentences according to the rules of good and correct Indonesian. The method used is a literature study, collecting and analyzing various theories related to grammar and sentence structure. The results of the discussion indicate that the use of effective sentences is crucial in various forms of writing, whether academic, professional, or general, because it can improve the quality of writing, clarify intent, and enhance the writer's credibility. In conclusion, mastering effective sentences is a fundamental skill required for effective and efficient communication.